Binding of Phage-Encoded FlaGrab to Motile Campylobacter jejuni Flagella Inhibits Growth, Downregulates Energy Metabolism, and Requires Specific Flagellar Glycans - Sacher, Jessica C.; Shajahan, Asif; Butcher, James; Patry, Robert T.; Flint, Annika; Hendrixson, David R.; Stintzi, Alain; Azadi, Parastoo; Szymanski, Christine M. (Frontiers in Microbiology, 2020)
Many bacterial pathogens display glycosylated surface structures that contribute to virulence, and targeting these structures is a viable strategy for pathogen control. The foodborne pathogen Campylobacter jejuni expresses a vast diversity of flagellar glycans, and flagellar glycosylation is essential for its virulence. Little is known about why C. jejuni encodes such a diverse set of flagellar glycans, but it has been hypothesized that evolutionary pressure from bacteriophages (phages) may have contributed to this diversity. However, interactions between Campylobacter phages and host flagellar glycans have not been characterized in detail. Previously, we observed that Gp047 (now renamed FlaGrab), a conserved Campylobacter phage protein, binds to C. jejuni flagella displaying the nine-carbon monosaccharide 7-acetamidino-pseudaminic acid, and that this binding partially inhibits cell growth. However, the mechanism of this growth inhibition, as well as how C. jejuni might resist this activity, is not well understood. Here we use RNA-Seq to show that FlaGrab exposure leads C. jejuni 11168 cells to downregulate expression of energy metabolism in a flagellar motor-dependent manner, which is consistent with a model whereby FlaGrab binding transmits a signal through flagella that leads to retarded cell growth. Using immunogold labeling and transmission electron microscopy, we identify two C. jejuni strains naturally resistant to FlaGrab binding. Through genetic analysis and mass spectrometric analysis of the flagellar glycans of these strains, we highlight possible roles for the acetamidino-pseudaminic acid transferase gene pseD (including possible phase-variable expression), for motility-associated (maf) and DUF2920-containing genes, and for display of as-yet uncharacterized flagellar glycans in C. jejuni resistance to Gp047 binding. Overall, we have further characterized the interaction between the phage-encoded flagellar glycan-binding protein and C. jejuni, both in terms of mechanism of action and mechanism of resistance. Our results suggest that C. jejuni encodes as-yet unidentified mechanisms for generating flagellar glycan diversity, and point to phage proteins as an exciting lens through which to study bacterial surface glycans.